Investigating the Factors Affecting Foreign Direct Investment in Selected Muslim Countries: A Panel Data Approach - Saeid Mahmoudi; Nasser Nasiri; Saeid Hajihassaniasl (Türkiye İslam İktisadı Dergisi)
This paper attempts to test the effects of foreign direct investment on selected Islamic countries by using spatial econometric analysis. For this purpose, foreign direct participation and investment data from selected countries were used as panel data between 2000-2013 years period. The foreign direct investment equation is estimated using static (fixed and random effects) and dynamic (Generalized Method of Moments) methods as panel data in both conventional and spatial econometric models. The results of the estimated model show the existence of spatial correlations between selected countries and hence the use of this type of estimation is justified. On the other hand, the variables of degree of openness of the economy and economic security have a positive and significant effect on attracting foreign direct investment in the studied countries while inflation rate, economic growth and human capital solely have no significant effect on foreign direct investment in these countries.